The effect of nitrogen fertilization and water stress on stomatal aperture, chlorophyll content and proline accumulation of Napier grass (Pennisetum purpureum Schum) - . Budiman (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2013)
The objective of the study was to determine the effect of nitrogen fertilization and water stress on the stomatal aperture, chlorophyll and proline accumulation of Napier grass (Pennisetum purpureum Schum.) The effect of water stress and nitrogen fertilizer levels were evaluated within an arrangement of Completely Randomized Design with factorial pattern (2x3). The variables observed were stomatal aperture, total chlorophyll and proline content. The results showed interaction between water stress and the level of fertilization. Interaction between water stress with nitrogen fertilization showed that the stomatal openings were more narrow (P<0.05) in water stressed plants compared to plants with excess water and that decreased stomatal aperture was not significant (P>0.05) with increasing levels of nitrogen fertilization either with sufficient water or with water stress. The exception is treatment of enough water and fertilizer 250 kg N/ha (P<0.05) where stomatal aperture decreased compared with no fertilizer. The total chlorophyll content of both the sufficiently watered and the water stressed Napier grass on nitrogen fertilizer rose with increasing doses of nitrogen fertilizer. The conditioning of water stress with fertilizer dose of 0 kg N/ha and 150 kg N/ha did not increase the total chlorophyll, however a dose of 250 kg N/ha resulted in an increase of total chlorophyll (P<0.05). Interaction between water stress and nitrogen fertilizer levels showed that the content of proline rose (P<0.05) with increasing levels of nitrogen fertilization, as well as with water stress treatment (P<0.05). It is concluded that water stress on Napier grass plants lowers stomatal aperture width, but increases proline accumulation and nitrogen fertilizer increases total chlorophyll and proline accumulation. There was an interaction between nitrogen fertilizer with water stress.